World Management of Geminiviruses - Rojas, Maria R; Macedo, Monica A; Maliano, Minor R; Soto-Aguilar, Maria; Souza, Juliana O; Briddon, Rob W; Kenyon, Lawrence; Rivera Bustamante, Rafael F; Zerbini, F Murilo; Adkins, Scott; Legg, James P; Kvarnheden, Anders; et al. (Annual review of phytopathology, 2018)
Management of geminiviruses is a worldwide challenge because of the widespread distribution of economically important diseases caused by these viruses. Regardless of the type of agriculture, management is most effective with an integrated pest management (IPM) approach that involves measures before, during, and after the growing season. This includes starting with resistant cultivars and virus- and vector-free transplants and propagative plants. For high value vegetables, protected culture (e.g., greenhouses and screenhouses) allows for effective management but is limited owing to high cost. Protection of young plants in open fields is provided by row covers, but other measures are typically required. Measures that are used for crops in open fields include roguing infected plants and insect vector management. Application of insecticide to manage vectors (whiteflies and leafhoppers) is the most widely used measure but can cause undesirable environmental and human health issues. For annual crops, these measures can be more effective when combined with host-free periods of two to three months. Finally, given the great diversity of the viruses, their insect vectors, and the crops affected, IPM approaches need to be based on the biology and ecology of the virus and vector and the crop production system. Here, we present the general measures that can be used in an IPM program for geminivirus diseases, specific case studies, and future challenges.